Implementing Character Education in Children through Education Madrasah Diniyah Awaliyah in Desa Emplasmen Sidamanik, Simalungun - Febri Nanda Monalisa; Syafri Fadillah Marpaung; Ahmad Raihan Azizi (Universitas Muhammadiyah Enrekang, 2024)
Madrasah Diniyah Awaliyah (MDA) in Emplasmen Sidamanik Village emphasizes strengthening the values of Islamic education with a focus on children aged 7 years and over. These values, especially faith, are considered the basic philosophy of the educational approach in this village, requiring time and patience to cultivate. The Prophet made it mandatory to teach prayer to children aged 7 years, showing the importance of building a religious foundation from an early age. Even though at first a child's understanding may be mechanical, instilling these values from the start is considered crucial, because with repetition and reinforcement, these values will be digested later. The role of parents is very important in introducing, discussing and reinforcing these values at home, forming the child's moral foundation until the end of life. Children after learning at MDA experience cognitive, spiritual, social and emotional development which reflects the positive results of holistic and comprehensive learning methods, creating a generation that understands religion, has character and is able to apply Islamic teachings in everyday life.